Endurance Training Alters Skeletal Muscle MCT Contents in T2DM Men - Opitz, D.; Lenzen, E.; Schiffer, T.; Hermann, R.; Hellmich, M.; Bloch, W.; Brixius, K.; Brinkmann, C. (International Journal of Sports Medicine, 2014)
Patients suffering from type 2 diabetes mellitus (T2DM) often exhibit chronic elevated lactate levels which can promote peripheral insulin resistance by disturbing skeletal muscle insulin-signaling. Monocarboxylate transporter (MCT) proteins transfer lactate molecules through cellular membranes. MCT-1 and MCT-4 are the main protein isoforms expressed in human skeletal muscle, with MCT-1 showing a higher affinity (lower Km) for lactate than MCT-4. T2DM patients have reduced membranous MCT-1 proteins. Consequently, the lactate transport between muscle cells and the circulation as well as within an intracellular lactate shuttle, involving mitochondria (where lactate can be further metabolized), can be negatively affected. This study investigates whether moderate cycling endurance training (3 times per week for 3 months) can change skeletal muscle MCT contents in T2DM men (n=8, years=56±9, body mass index (BMI)=32±4 kg/m2). Protein content analyses (immunohistochemical stainings) were performed in biopsies taken from the vastus lateralis muscle. Intracellular MCT-1 proteins were up-regulated (relative increase+89%), while intracellular MCT-4 contents were down-regulated (relative decrease − 41%) following endurance training. Sarcolemmal MCT-1 and MCT-4 did not change. The question of whether the training-induced up-regulation of intracellular MCT-1 leads to an improved lactate transport (and clearance) in T2DM patients requires further research.
Keywords: MCT; exercise; diabetes; lactate